The rental sector and the housing block in STREAM - Brian Micallef; Nathaniel Debono (Central Bank of Malta, 2020)
In recent years the housing market in Malta has been characterised by significant demand and supply developments reflecting strong economic and population growth. While the determinants of house prices in Malta have long been studied and documented, much less is known about private sector rents, partly due to the absence of official statistics on this sector. This paper uses information from the Estate Agency Rent Survey to construct a proxy for private sector rents in Malta. Using this index, a specification for private sector rents is specified using an error-correction modelling approach and added to the housing block in STREAM. Consistent with theoretical expectations, a one-to-one relationship between rents and house prices is confirmed in the long-run. Short-run dynamics are affected by past developments in rents, the foreign population, the number of tourist nights stayed in private accommodation and the housing stock per household. The housing block in STREAM is modified to accommodate for the inclusion of the rents equation, with the specifications for house prices and dwelling investment modelled following a stock-flow framework in line with Gatt et al. (2018). A simulation using STREAM illustrates the impact on the main macroeconomic variables following a hypothetical 10% increase in real housing investment.
Keywords: R21; R31; E37; 330; Rents; House prices; Housing investment; Housing market; Malta